An Instructional model based on self-efficacy theory and autonomous learning to enhance Chinese speaking ability of undergraduate students - Yuwadee Tirataradol (2012)
The purposes of this research were 1) to develop an instructional model based on self-efficacy theory and autonomous learning so as to enhance Chinese speaking ability of undergraduate students and 2) to evaluate the efficiency of the developed instructional model. This study was conducted in 2 phases. The first phase was dedicated to the development of the Chinese language instructional model. The second phase was carrying out the experiment of the developed instructional model. The sample of this experiment was engineering students in Mahidol University, Thailand, studying Chinese I as an elective course in the second semester of academic year 2010. Five research tools used in this study were Chinese speaking ability test, self-efficacy test, instructional conditions record sheet, autonomous learning record sheet, and the questionnaire on the opinion about the developed instructional model. Data analysis used in this study included means, percent, standard deviation, and content analysis. The statistics used in this study were t-test independent and t-test dependent at the significant level of 0.5.